The role of immune checkpoint inhibitors in the first-line treatment for patients with advanced biliary tract cancer: a systematic review and meta-analysis of randomized trials - Vitale, Elsa; Rizzo, Alessandro; Maistrello, Lorenza; Nardulli, Patrizia; Talienti, Tiziana; Quaresmini, Davide; De Summa, Simona; Massafra, Raffaella; Silvestris, Nicola; Brunetti, Oronzo (Frontiers in Oncology, 2024)
Background We performed a systematic review and meta-analysis to further explore the impact of the addition of immunotherapy to gemcitabine–cisplatin as first-line treatment for advanced biliary tract cancer (BTC) patients. Methods Literature research was performed, and hazard ratio values and 95% confidence intervals were calculated. Heterogeneity among studies was assessed using the tau-squared estimator (τ2). The total Cochrane Q test (Q) was also assessed. The overall survival rate, objective response rate, and progression-free survival in the selected studies were assessed. Results A total of 1,754 participants were included. Heterogeneity among the studies selected was found to be non-significant (p = 0.78; tau2 = 0, I2 = 0%). The model estimation results and the forest plot suggested that the test for the overall effect was significant (Z = −3.51; p< 0.01). Conclusion The results of the current meta-analysis further confirm the role of immune checkpoint inhibitors plus gemcitabine–cisplatin as the new standard first-line treatment for advanced BTC patients. Systematic review registration https://www.crd.york.ac.uk/prospero, identifier CRD42023488095.